Answer:
![(x+1)^2 + (y-1)^2 = 16](https://img.qammunity.org/2021/formulas/mathematics/college/j3m8947qby7ha2yp91tlij0be926m0vqhn.png)
And the general formula for a circle is given by this expression:
![(x-h)^2 +(y-k)^2 = r^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/404ameg60kum5hckbs5pzxk3xlnowr1ul4.png)
With the center (h,k) and the radius r. If we compare this general expression with the formula that we obtain in (1) we see that :
![h = -1, k =1 , r =4](https://img.qammunity.org/2021/formulas/mathematics/college/wjzkm6x0ggtw3d50mzlu15y6mtjbpv33uv.png)
So then the best solution for this cae would be:
b. center: (-1,1)
radius =4
Explanation:
For this case we have the following equation given:
![x^2 +2x + y^2 -2y -14=0](https://img.qammunity.org/2021/formulas/mathematics/college/ba6a8rcinkaq0jcphc5nyoiac2k8heyf3u.png)
And we can complete the squares for this case like this:
![x^2 +2x +(2/2)^2 +y^2 -2y +(2/2)^2 =14 +1+1](https://img.qammunity.org/2021/formulas/mathematics/college/dvqj8ws1e5mlukda77whyzvcyu9rlxqeob.png)
![(x^2 +2x +1) +(y^2 -2y +1) =16](https://img.qammunity.org/2021/formulas/mathematics/college/gjr4vpv9dqhsag4im5gn38ik6tolhwybmd.png)
Now we can rewrite the last expression like this:
![(x+1)^2 + (y-1)^2 = 16](https://img.qammunity.org/2021/formulas/mathematics/college/j3m8947qby7ha2yp91tlij0be926m0vqhn.png)
And the general formula for a circle is given by this expression:
![(x-h)^2 +(y-k)^2 = r^2](https://img.qammunity.org/2021/formulas/mathematics/high-school/404ameg60kum5hckbs5pzxk3xlnowr1ul4.png)
With the center (h,k) and the radius r. If we compare this general expression with the formula that we obtain in (1) we see that :
![h = -1, k =1 , r =4](https://img.qammunity.org/2021/formulas/mathematics/college/wjzkm6x0ggtw3d50mzlu15y6mtjbpv33uv.png)
So then the best solution for this cae would be:
b. center: (-1,1)
radius =4